2014
DOI: 10.1002/hep.27366
|View full text |Cite
|
Sign up to set email alerts
|

Concordance of sustained virological response 4, 12, and 24 weeks post‐treatment with sofosbuvir‐containing regimens for hepatitis C virus

Abstract: Historically, clinical trials of regimens to treat chronic infection with hepatitis C virus (HCV) have used, as their primary efficacy endpoint, a sustained virological response (SVR)-defined as HCV RNA levels below a designated threshold of quantification-24 weeks after the end of treatment (SVR24). More recently, regulatory authorities have begun to accept SVR at 12 weeks post-treatment (SVR12) as a valid efficacy endpoint because of its high rate of concordance with SVR24. However, the concordance between S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
142
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(158 citation statements)
references
References 9 publications
10
142
0
4
Order By: Relevance
“…A key goal of hepatitis C virus (HCV) therapy is to achieve a sustained virologic response (SVR), defined as undetectable serum HCV RNA levels 12 weeks post end of treatment (EOT) [4]. Even with newly approved oral direct-acting antiviral (DAA) regimens replacing interferon (IFN)-based therapy [1,[5][6][7][8], HCV therapy remains lengthy (~12 weeks) and expensive.…”
mentioning
confidence: 99%
“…A key goal of hepatitis C virus (HCV) therapy is to achieve a sustained virologic response (SVR), defined as undetectable serum HCV RNA levels 12 weeks post end of treatment (EOT) [4]. Even with newly approved oral direct-acting antiviral (DAA) regimens replacing interferon (IFN)-based therapy [1,[5][6][7][8], HCV therapy remains lengthy (~12 weeks) and expensive.…”
mentioning
confidence: 99%
“…Recent studies demonstrated that SVR12 (HCV RNA \25 IU/mL 12 weeks after end of treatment) had positive predictive values (PPV) of [98 % for SVR24, regardless of whether therapy was interferon based or DAA interferon free [174,175]. SVR12 is currently widely used as the primary endpoint of clinical trials and regulatory approval for DAA-containing regimens.…”
Section: #8 Consensus Statements and Recommendations On Prevention Ofmentioning
confidence: 99%
“…However, with direct-acting agents, that are so much more potent, it has been shown that the viral clearance can be assessed 12 weeks after therapy. Thus, SVR12 is the currently advised standard [14,15]. At the time when interferon (IFN)-α was approved as the first anti-HCV drug in the SVR, it was only achieved in 2-7% of treated patients [16].…”
Section: Changes In the Hcv Treatment Goals And Hcv Treatment Timelinmentioning
confidence: 99%
“…Even though some studies suggested that HCV patients with the IL28B TT genotype had reduced therapeutic efficacy of some DAA regimens, IL28B genotyping did lose importance in the IFN-free era [15,29,92]. Furthermore, in African-American patients infected with HCV GT1a, ribavirin is recommended to be added to ombitasvir plus paritaprevir/ritonavir or dasabuvir treatment regimens to improve cure rates [93].…”
Section: Hcv Pharmacogenetic Testing In the Ifn-free Eramentioning
confidence: 99%